Odpowiedzi

2009-12-08T20:07:59+01:00
4(x+2)=1-5y
{3(y+2)=3-2x

4x+8=1-5y
3y+6=3-2x

4x = 1-5y -8 /4
3y+6=3-2x

x=1/4 - 5/4 - 2
3y+6=3-2x

3y+6=3-2(1/4-5/4-2)
3y+6= 3 - 1/2 + 5/2 + 4
3y = 11/2 / : 3
y = 11/6

3(x-1)=4y+1
5(y-1)=x+1

3x - 3 = 4y+1
5y-5=x+1

3x - 3 = 4y+1
5y-5-1=x

3(5y-5-1)-3=4y+1
15y-15-3-3=4y+1
15y-4y=1+15+3+3
11y=24 / :11
y = 24/11

nie wiem czy dobrze , bo już późno :D
2009-12-08T20:10:12+01:00
4(x+2)=1-5y
3(y+2)=3-2x

4x + 8 = 1 - 5y
3y + 6 = 3 - 2x

4x = -7 + 5y | :4
3y + 6 = 3 - 2x

x = -7/4 + 5y/4
3y + 6 = 3 - (-7/4 + 5y/4)

x = -7/4 + 5y/4
3y + 6 = 3 + 1 3/4 - 5y/4

x = -7/4 + 5y/4
3y + 5y/4 = 4 3/4 - 6

x = -7/4 + 5y/4
3y + 5y/4 = -1 3/4 | *4

x = -7/4 + 5y/4
12y + 5y = -7

x = -7/4 + 5y/4
17y = -7

Dalej nie umiem :P
2009-12-08T20:18:37+01:00
3(x-10)=4y+1
5(y-1)=x+1

3x-3=4y+1
5y-5=x=1

3x-4y=4
5y-x=6

3x-4y=4
-x=6-5y/ :(-1)


3x-4y=4
x=-6+5y

3(-6+5y)-4y=4
x=-6=5y

-18+15y-4y=4
x=-6=5y

11y=22 /(-1)
x=-6+5y

y=2
x=-6+5y

x=-6+10
y=2

x=4
y=2